PENGARUH KOMPOSISI CAMPURAN LIMBAH PENYULINGAN SEREH WANGI, SERBUK KAYU, DAN BAHAN PENGIKAT TANAH LIAT TERHADAP KUALITAS OBAT NYAMUK BAKAR - Sugiarto, Bambang; Kalsum, Ummi; Wirawan, Kristuaji Andre; Widayati, Tunjung Wahyu (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2024)
Mosquito coils contain chemicals that are unsafe if used for a long period of time, so alternative natural ingredients are needed to minimize the effects that can be caused. So far, solid waste from distilleries has only been used as fuel for refining or as organic fertilizer. Citronella waste contains ingredients such as citronellal and geraniol which can function as a mosquito repellent. This research aims to determine how to make mosquito coils from citronella waste and wood dust, to determine the effect of the composition of citronella and wood powder (in weight) with a ratio of 70:30, 60:40, 50:50, 40:60, 30 :70, determine the effect of adding binder with a weight of 0, 3, 6, 9, 12 grams on the composition of mosquito coils, and determine the optimal composition of the composition of mosquito coils. The test methods used are water content testing, ash content testing, burning rate testing, burning time and efficacy testing. From the results of the tests that have been carried out, optimal results were obtained, namely in the treatment with a ratio of citronella waste : sawdust 30:70 and the optimum weight of clay was 9 grams.